Optimizing the Role of Nganjuk Government in Online Learning during the Pandemic - Maya Puspita Dewi; Muh Barid Nizarudin Wajdi (STAI Miftahul Ula Nganjuk, 2021)
The article aims to identify the role of the Nganjuk district government toward Online learning in the pandemic. The author uses descriptive qualitative methods by describing and explaining comprehensively and specifically related to current events or phenomena, so that the role of the government can be done to the maximum As a result of the discussion found that in its implementation, the role of the government brings a significant impact both for children as students and teachers as teachers, especially in addressing the lack of adequate supporting facilities and limited understanding of technology access and internet networks become the main obstacles felt by both parties. the policy can be analyzed based on Van Meter and Van Horn theories. The theory in policy implementation is to look at the implementation achievements of 6 variables, including; (1). Standards and Policy Objectives, (2) Resources, (3) Characteristics of Implementing Organizations, (4) Communication, (5) Attitudes of Implementers, (6). Social, economic, and political environment. All variables show the achievement of online learning implementation during the Covid-19 pandemic in Nganjuk Regency.